2010
DOI: 10.1144/0070037
|View full text |Cite
|
Sign up to set email alerts
|

North Sea hydrocarbon systems: some aspects of our evolving insights into a classic hydrocarbon province

Abstract: A review is given of the development of the understanding of the structure and stratigraphy of a classic petroleum province through 35 years of NW European Petroleum Geology Conferences, using new examples to illustrate the interplay between tectonics and sedimentation in the development of some of the major hydrocarbon plays. Cimmerian tectonics is discussed, with regard to the evidence for regional-scale truncation beneath the Mid Cimmerian unconformity, and the stratal motifs characteristic of rifting assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Firstly, the complex structures formed as a result of the interaction and competition between mantle and crustal weaknesses in our reference models from Series A (Figures 7a-f and 8a-f) highlight the suggestion by Reeve et al (2015) and Zwaan et al (2021a) that complex rift structures with multiple structural orientations can be formed during a single phase of rifting. As such, when encountering such rift arrangements in the field, as for instance in the North Sea (Erratt et al, 1999(Erratt et al, , 2010 and references therein), there is no direct need to invoke changes in the divergence direction over time, and divergence was also not necessarily (sub-)orthogonal to either of the normal faults.…”
Section: Implications For Interpreting Natural Rift Systemsmentioning
confidence: 99%
“…Firstly, the complex structures formed as a result of the interaction and competition between mantle and crustal weaknesses in our reference models from Series A (Figures 7a-f and 8a-f) highlight the suggestion by Reeve et al (2015) and Zwaan et al (2021a) that complex rift structures with multiple structural orientations can be formed during a single phase of rifting. As such, when encountering such rift arrangements in the field, as for instance in the North Sea (Erratt et al, 1999(Erratt et al, , 2010 and references therein), there is no direct need to invoke changes in the divergence direction over time, and divergence was also not necessarily (sub-)orthogonal to either of the normal faults.…”
Section: Implications For Interpreting Natural Rift Systemsmentioning
confidence: 99%
“…16) that opened along pre-existing tectonic lineaments inherited from the Caledonian orogeny (Bartholomew et al, 1993). A first rift phase in the Triassic formed the rough Central Graben structure was reactivated during subsequent Late Jurassic-Early Cretaceous extension, probably under orthogonal or near-orthogonal extension conditions (Erratt et al, 1999(Erratt et al, , 2010. While deep rift basins formed during these rifting events, leading to the deposition of world-class Upper Jurassic hydrocarbon source rocks (Gautier, 2005), the intervening highs remained emergent and subjected to erosion.…”
Section: Rift Pass Structuresmentioning
confidence: 99%
“…Extension is generally considered to be (sub-)perpendicular to the strike of normal faults; hence multiple structural orientations within a rift basin may indicate a change in extension direction over time, as for instance proposed for the North Sea Rift, the Main Ethiopian Rift and Turkana Depression in the East African Rift, and the Labrador Sea (e.g. Bonini et al, 1997;Erratt et al, 1999Erratt et al, , 2010Heron et al, 2019;Wang et al, 2021). Yet it has also been shown that this assumption is often not fully valid due to the influence of structural inheritance, oblique extension and associated regional stress field distributions (e.g.…”
Section: Introductionmentioning
confidence: 99%